A novel multi-affinity tag system to produce high levels of soluble and biotinylated proteins in Escherichia coli - Ashraf, S.Salman; Benson, R.Edward; Payne, E.Sturgis; Halbleib, Cale M; Grøn, Hanne (Protein expression and purification, 2004)
We describe here a novel multi-affinity tag vector that can be used to produce high levels of soluble, in vivo biotinylated proteins in Escherichia coli. This system combines the solubility-enhancing ability of maltose-binding protein (MBP), the versatility of the hexahistidine tag (His 6), and the site-specific in vivo biotinylation of a 15-amino acid tag (AviTag). We used this multi-tag system in an attempt to improve expression levels of two prokaryotic proteins—elongation factor Tu (TufB) and DNA gyrase subunit A (GyrA)—as well as two eukaryotic nuclear receptors—glucocorticoid receptor (GR) and small heterodimer partner (SHP). The multi-tag system not only vastly improved the expression of the two prokaryotic proteins tested, but also yielded complete, site-specific, in vivo biotinylation of these proteins. The results obtained from the TufB expression and purification are presented and discussed in detail. The nuclear receptors, though soluble as fusion partners, failed to remain soluble once the MBP tag was cleaved. Despite this limitation of the system, the multi-affinity tag approach is a useful system that can improve expression of some otherwise insoluble or poorly expressing proteins, to obtain homogeneous, purified, fully biotinylated protein for downstream applications.